Cod liver oil nano-structured lipid carriers (Cod-NLCs) as a promising platform for nose to brain delivery: Preparation, in vitro optimization, ex vivo cytotoxicity & in vivo biodistribution utilizing radioiodinated zopiclone - Esraa Taha; Samia A. Nour; Wael Mamdouh; Adli A. Selim; Mohamed M. Swidan; Ahmed B. Ibrahim; Marianne J. Naguib (Elsevier, 2023)
Nano-structured lipid carriers containing zopiclone were prepared as a targeted drug delivery system to convey zopiclone directly to brain via nasal route. Nano-structured lipid carriers were constructed adopting hot emulsification-ultrasonication method using palmitic acid in place of the solid lipid, cod liver oil as liquid lipid, and poloxamer 407 as a surfactant. A three-factor three-level central composite face-centered design was used to optimize the formulated nano-structured lipid carriers. The independent factors were lipid amount (X1), surfactant amount (X2), and sonication time (X3). The examined responses were entrapment efficiency (EE,Y1,%), particle size (PS,Y2,nm), zeta potential(mV), polydispersity index(PDI,Y3), in vitro release(Q8h,Y4,%) and dissolution efficiency (DE,Y5,%). The optimum formula showed high entrapment efficiency of 94.31% ± 2.44, in vitro drug release of 83.89% ± 1.77 with dissolution efficiency equals 88.63% ± 2.01, small particle size of 71.27 nm ± 13.57 and low polydispersity index 0.097 ± 0.15. In vivo biodistribution in mice was evaluated by a radiobiological technique using radioiodinated zopiclone([131I]iodo-ZP). Results revealed the superiority of the intranasal route to deliver zopiclone directly to brain faster and higher brain uptake (6.9 ± 1.02%ID/g at 5 min post-administration). The current study confirmed that intranasal administration of nano-structured lipid carriers had great potential as an effective tool for targeted brain zopiclone delivery for insomnia treatment.